Comparative physicochemical analysis of suspended and immobilized cultivation of Chlorella sp. - Zeng, X.; Danquah, Michael; Halim, R.; Yang, S.; Chen, X.; Lu, Y. (Wiley, 2013)
Background: Immobilized cultivation of microorganisms is gaining interest in the microalgae industry. In this study, a novel microalgae polymeric carrier, sodium cellulose sulphate/poly-dimethyl-diallyl-ammonium chloride (NaCS-PDMDAAC) capsule system, was employed to immobilize Chlorella sp. Microalgae cultivation was performed under immobilized and suspended conditions, and the resulting cells were characterized biochemically and physically. Results: Experimental results indicated that microalgae cells cultivated under NaCS-PDMDAAC immobilized conditions have a robust morphology, a smaller average cell size of 2.92 µm and a higher Zeta potential of - 17.10 mV than the suspended cells with a cell size of 6.81 µm and Zeta potential of - 32.90 mV. The immobilized microalgae cells displayed a total lipid content of 14.85%, and a chlorophyll content of 3.36%, slightly higher than those obtained from the suspended cells. CONCLUSION: These differences are critical to further explore the impact of immobilized microalgae cultivation systems for specific biotechnological applications. © 2012 Society of Chemical Industry.